Analysis of Cylinder Pressure and Heat Release Rate Variation in Diesel Engine Fueled with Croton Macrostachyus (CMS) Seed Oil Biodiesel as an Alternative Fuel - Adem Siraj Mohammed; Venkata Ramayya Ancha; Samson Mekbib Atnaw; Melaku Desta; Ramchandra Bhandari (Energies)
Despite its higher density, viscosity, and lower calorific value, biodiesel has been explored as an alternative energy source to diesel fuel. This study investigated biodiesel produced from croton macrostachyus (CMS) seed, a non-edible feedstock. The research aimed to experimentally analyze cylinder pressure, heat release rate, and ignition delay, as well as engine performance and emission characteristics, at a constant speed of 2700 rpm under varying loads (0–80%) using diesel, B10, B15, B20, and B25 blended fuels. Among the tested blends, B25 exhibited superior performance, achieving the highest peak cylinder pressure (CP) of 58.21 bar and a maximum heat release rate (HRR) of 543.9 J/CA at 80% engine load. Conversely, B20 at 60% engine load, followed by B25 and pure diesel at 80% engine load, demonstrated the shortest ignition delay (ID) and the most advanced start of combustion (SoC). Compared to the biodiesel blends, pure diesel showed: a 5.5–14% increase in brake thermal efficiency (BTE), a 17–26% decrease in brake-specific fuel consumption (BSFC), and a 7–12% reduction in exhaust gas temperature (EGT). Regarding emissions, carbon monoxide (CO) and hydrocarbon (HC) emissions were lower for pure diesel, while carbon dioxide (CO2) and nitrogen oxide (NOx) emissions were higher for biodiesel blends, attributed to their inherent oxygen content. In conclusion, CMS biodiesel displays promising characteristics, suggesting its potential suitability for use in internal combustion engines.